The EMA Review of Mylotarg (Gemtuzumab Ozogamicin) for the Treatment of Acute Myeloid Leukemia. (21st March 2019) - Ali, Sahra; Dunmore, Helen‐Marie; Karres, Dominik; Hay, Justin L.; Salmonsson, Tomas; Gisselbrecht, Christian; Sarac, Sinan B.; Bjerrum, Ole W.; Hovgaard, Doris; Barbachano, Yolanda; Nagercoil, Nithyanandan; Pignatti, Francesco
Abstract: : On February 22, 2018, the Committee for Medicinal Products for Human Use (CHMP) adopted a positive opinion, recommending the granting of a marketing authorization for the medicinal product gemtuzumab ozogamicin (Mylotarg; Pfizer, New York City, NY), intended for the treatment of acute myeloid leukemia. Mylotarg was designated as an orphan medicinal product on October 18, 2000. The applicant for this medicinal product was Pfizer Limited (marketing authorization now held by Pfizer Europe MA EEIG). The demonstrated benefit with Mylotarg is improvement in event‐free survival. This has been shown in the pivotal ALFA‐0701 (MF‐3) study. In addition, an individual patient data meta‐analysis from five randomized controlled trials (3, 325 patients) showed that the addition of Mylotarg significantly reduced the risk of relapse (odds ratio [OR] 0.81; 95% CI: 0.73–0.90; p = .0001), and improved overall survival at 5 years (OR 0.90; 95% CI: 0.82–0.98; p = .01) [Lancet Oncol 2014;15:986–996]. The most common (>30%) side effects of Mylotarg when used together with daunorubicin and cytarabine are hemorrhage and infection. The full indication is as follows: "Mylotarg is indicated for combination therapy with daunorubicin (DNR) and cytarabine (AraC) for the treatment of patients age 15 years and above with previously untreated, de novo CD33‐positive acute myeloid leukemia (AML), except acute promyelocytic leukemia (APL)." The objective of this article is to summarize the scientific review done by the CHMP of the application leading to regulatory approval in the European Union. The full scientific assessment report and product information, including the Summary of Product Characteristics, are available on the European Medicines Agency website (www.ema.europa.eu ). Abstract : This article reports on the first approved immunotherapy for acute myeloid leukemia.